Reforming reformed church polity in South Africa's Black Reformed Churches (RCSA) : an African decolonial approach - Duncan, Graham A (University of Pretoria, 2026)
Dissertation (MTh (MTh (Church History and Church Policy))--University of Pretoria, 2024.